THE EFFECT OF TOMAN (Chana Micropetes) EXTRACT ON THE IMPROVEMENT OF ALBUMIN LEVELS IN MENCIT/MICE (Mus musculus) - Pipit Festi W (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2020)
Hypoalbuminemia is a condition in which albumin levels are less than 3.8 g / dl. Management of hypoalbumin can be done on a  high high in protein such as toman fish extract (Chana Micropetes). Toman fish extract contains globular protein which can be used as an alternative diet in increasing albumin levels. The purpose of this study was to determine the effect of toman fish extract on increasing albumin levels in mencit (Mus musculus).               This research is an experimental research design with Pretest-Posttest Control Group Design. Samples using Mus musculus with the criteria of male sex, body weight 25-40 grm and 2 months old. The number of samples consisted of 32 animals consisting of 2 groups, 16 control groups and 16 treatment groups. Intervention by giving toman fish extract for 14 days. Research instruments, albumin levels and observation sheets. Data were tested statistically with Independent Sample t Test.               The results, this study showed the average value of albumin levels was 5.60 gr / dl in the treatment group so that an increase in albumin levels. There was a significant effect (p = 0,000 <α = 0.05) between the administration of toman fish extract to the increase in albumin levels in mencit (Mus Muculus).               Conclusion, giving toman fish extract can increase albumin levels in mencit. So that toman fish extract can be used as a high-protein alternative diet for hypoalbumin sufferers.Keywords: hypoalbumin, toman fish, (Chana Micropetes).